Community Pharmacist Consultation Service: A Survey Exploring Factors Facilitating or Hindering Community Pharmacists' Ability to Apply Learnt Skills in Practice - Elizabeth M. Seston; Chiamaka Julia Anoliefo; Jinghua Guo; Joanne Lane; Chikwado Okoro Aroh; Samantha White; Ellen I. Schafheutle (MDPI AG, 2022)
Background: The NHS Community Pharmacist Consultation Service (CPCS) offers patients requiring urgent care a consultation with a community pharmacist, following referral from general practice or urgent care. The study explored the impact of undertaking a Centre for Pharmacy Postgraduate Education (CPPE) CPCS learning programme, and barriers and enablers to CPCS delivery. Methods: CPPE distributed an online survey to those who had undertaken their CPCS learning. The survey explored participants' knowledge, confidence and application of taught skills/tools, including clinical history-taking, clinical assessment, record keeping, transfer of care, and Calgary-Cambridge, L(ICE)F and SBARD communication tools. Details on barriers and enablers to CPCS delivery were also included. Results: One-hundred-and-fifty-nine responses were received (response rate 5.6%). Knowledge of, and confidence in, taught skills were high and respondents reported applying skills in CPCS consultations and wider practice. Barriers to CPCS included a lack of general practice referrals, staffing levels, workload, and GP attitudes. Enablers included a clear understanding of what was expected, minimal concerns over indemnity cover and privacy, and positive patient attitudes towards pharmacy. Conclusion: This study demonstrates that community pharmacists can extend their practice and contribute to the enhanced provision of urgent care in England. This study identified barriers, both interpersonal and infrastructural, that may hinder service implementation.